Peran Komite Sekolah dalam Meningkatkan Mutu Pendidikan pada Jenjang SMP di Kabupaten Konawe - Asra (FKIP, Universitas Lakidende Unaaha, 2015)
This study investigated the role of School Committee in improving the quality of education at junior high school level in Konawe Regency. It was proposed to uncover what the School Committee roles has done in improving senior high school quality in Konawe Regency. It was expected to improve the quality of education by endorsing the School Committee roles. This study used quantitative approach by survey method on the characteristics, actions, and opinions from a group of respondents as representative of the population. The information associated with the roles committee played in improving the quality of education in Konawe Regency. Data collection was conducted using list of questionnaire. There were 20 SMPs chosen as subject of study. The results showed that the roles the School Committee had played were at a good category. It had already played its role as Consideration Board in deciding school programs, determining to be involved in defining the teaching learning process in class, defining the curriculum, allocating the schools’ program budget as well involving in determining extension learning program. However, the role of committee as consideration board still needs to be maximized.